Heat treated hydrotalcite as support for lipase immobilization - Othman, Siti Salhah; Basri, Mahiran; Hussein, Mohd Zobir; Yap, Taufiq Yun Hin; Abdul Rahman, Mohd Basyaruddin; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar (Universiti Putra Malaysia Press, 2003)
Hydrotalcite (HT) and heat treated hydrotalcite (HTHT) with Mg2+:A1~ of ratio 4 were prepared by co-precipitating through continuous agitation and heating to 200°C, respectively. From the X-ray diffraction patterns of these materials, it was found that hydrotalcite had been successfully synthesized and the layered structure was not collapsed by the heat treatment up to 200°C. Lipase from Candida rugosa was then immobilized onto these materials, through the physical adsorption method. It was found that percentage of protein loading increases from HT (20%) to HTHT (40%). Their activities were tested by the esterification reaction of oleic acid and butanol in hexane. The immobilized enzymes were then characterized in terms of their thermal, solvent (hexane) and storage stability. Their various stabilities were comparatively higher than native lipase (NL).